THE CORRELATION OF OROMOTOR DYSFUNCTION TO ORAL HEALTH-RELATED QUALITY OF LIFE IN CHILDREN WITH DOWN SYNDROME - Nurdiana Dewi; Adhytya Suryo Kelana; Juliyatin Putri Utami (FKG ULM, 2024)
Background: The genetic condition known as Down syndrome (DS) is brought on by chromosome 21 trisomy. Children with DS frequently have oromotor dysfunctiont. Oromotor dysfunction in children with Down syndrome can lead to oral health issues and lower the oral health-related quality of life. Studies on the relationship between oromotor dysfunction and quality of life related to dental health in children with Down syndrome are still lacking, nevertheless. Objective: To analyze the correlation between oromotor dysfunction and oral health-related quality of life in children with DS. Methods: Total respondents used in this research was 30 children with DS and the parents in Banjarmasin Special Schools. Oromotor dysfunction was determined using the Oral Motor Assessment Scale (OMAS) and oral health-related quality of life was determined using the Modified Parent-Caregiver Perception Questionnaire (P-CPQ). The Spearman correlation test was used to analyze the correlation between oromotor dysfunction and oral health related quality of life in Down syndrome children. Results: The Spearman correlation test showed that there was a significant correlation between oromotor dysfunction and oral health-related quality of life in children with DS with a significance value of 0.000 (p <0.05) with the correlation coefficient of 0.637. Conclusion: There was a positive and strong correlation between oromotor dysfunction and oral health-related quality of life in children with DS. The weaker the oromotor function in children with Down syndrome is, the worse the oral health-related quality of life will be.Keywords: Down syndrome, oral health-related quality of life, oromotor dysfunction.